Fetal intracardiac rhabdomyoma in beckwith‐wiedemann syndrome. Issue 9 (18th April 2014) - Longardt, Ann Carolin; Nonnenmacher, Andreas; Graul‐Neumann, Luitgard; Opgen‐Rhein, Bernd; Henrich, Wolfgang; Bührer, Christoph; Hüseman, Dieter
ABSTRACT Fetal cardiac tumors are a rare finding in prenatal ultrasonography. Most of them are rhabdomyoma, which are thought to be pathognomonic for tuberous sclerosis complex. We present an infant with prenatally diagnosed cardiac rhabdomyoma (CR), who was found to suffer from Beckwith‐Wiedemann syndrome (BWS). This congenital overgrowth syndrome is characterized by macrosomia, macroglossia, omphalocele, hypoglycemia, and hemihypertrophy. BWS patients have an increased risk for formation of benign and malignant tumors, typically intra‐abdominally located, but, to the best of our knowledge, fetal CRs have not been reported before. BWS must be added to the list of differential diagnoses and to the prenatal counseling of the parents in cases of prenatal detection of CR. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:569–573, 2014